2002
DOI: 10.1093/gerona/57.8.m496
|View full text |Cite
|
Sign up to set email alerts
|

Age Influences the Outcome of a Slipping Perturbation During Initial But Not Repeated Exposures

Abstract: Older adults are more likely to fall upon initial, unexpected perturbation exposure, but, upon repeated exposure, healthy young and older adults rapidly learn to avoid falling at a similar rate. Healthy older adults appear fully capable of learning to better recover from or adjust to a perturbation through repeated exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 29 publications
5
104
1
2
Order By: Relevance
“…Numerous studies have been reported in which older adults subjected to slips using translating platforms. These studies have documented control of head and trunk motion [16]; initial "fall" incidence and ability to adapt [17]; postural responses and corrective balance strategy [18]. However, slips induced with translating platform limit the slipping foot motion to that allowed by the platform, whereas slips induced with slippery surfaces result in significant medially-and laterally-directed slipping foot motion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been reported in which older adults subjected to slips using translating platforms. These studies have documented control of head and trunk motion [16]; initial "fall" incidence and ability to adapt [17]; postural responses and corrective balance strategy [18]. However, slips induced with translating platform limit the slipping foot motion to that allowed by the platform, whereas slips induced with slippery surfaces result in significant medially-and laterally-directed slipping foot motion [19].…”
Section: Discussionmentioning
confidence: 99%
“…These goals would provide clinicians with information about the importance of the visual system and usefulness of repeated balance perturbations for rehabilitation. We hypothesize that there would be a correlation between tibialis anterior and gastrocnemius muscle activity and body movement and that this relationship might be affected by adaptation due to the online updating of motor performance Pavol et al, 2002) but should not be affected by the availability of visual information.…”
Section: Introductionmentioning
confidence: 99%
“…Further, empirical results show that experience or repeated practice causes a task-specific adaptation (Erni and Dietz, 2001;Pavol et al, 2002;Pai et al, 2003). Most of those studies indicated an improvement in locomotion mechanics.…”
mentioning
confidence: 99%